Influence of 1+ states on the gR-factors of ground band in isotopes of 160Dy and 170,174Yb - Okhunov, Abdurahim; Usmanov, Phazlitdin; Abu Kassim, Hasan (IOP PUBLISHING LTD, 2014)
In this work, non-adiabatic effects manifested in the magnetic properties of ground band in even–even deformed nuclei are studied. A simple phenomenological model, which takes into account the Coriolis mixing of states of the ground and Kπ = 1+ ν bands, is proposed. Using perturbation theory, corrections to the wave functions of states are determined. In addition, an analytical expression to determine the gR-factor of the states of ground rotational band is obtained. The decrease in gR-factor with increasing angular momentum I is discussed. The accuracy of the approximation is verified. The determined values of wave functions of different methods are found to be close to each other.